2011
DOI: 10.1029/2011ja016532
|View full text |Cite
|
Sign up to set email alerts
|

Energetic O+and H+ions in the plasma sheet: Implications for the transport of ionospheric ions

Abstract: [1] The present study statistically examines the characteristics of energetic ions in the plasma sheet using the Geotail/Energetic Particle and Ion Composition data. An emphasis is placed on the O + ions, and the characteristics of the H + ions are used as references. The following is a summary of the results. (1) (5) The O + -to-H + ratios of number and energy densities increase toward Earth during all solar phases, but most clearly during solar maximum. These results suggest that the solar illumination enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
80
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 44 publications
(68 reference statements)
9
80
2
Order By: Relevance
“…Kronberg et al (2012) showed that the O + /H + intensity at energies above 274 keV is between 0.5 and 1 and is much higher than the ratio at ∼10 keV which may result from a more efficient heating of O + ions than of H + ions. Maggiolo and Kistler (2014) and are in agreement with , , Ohtani et al (2011). These trends indicate that the mid tail O + density is more sensitive to geomagnetic activity than to solar EUV flux.…”
Section: Plasma Sheetsupporting
confidence: 76%
See 4 more Smart Citations
“…Kronberg et al (2012) showed that the O + /H + intensity at energies above 274 keV is between 0.5 and 1 and is much higher than the ratio at ∼10 keV which may result from a more efficient heating of O + ions than of H + ions. Maggiolo and Kistler (2014) and are in agreement with , , Ohtani et al (2011). These trends indicate that the mid tail O + density is more sensitive to geomagnetic activity than to solar EUV flux.…”
Section: Plasma Sheetsupporting
confidence: 76%
“…Lennartsson and Shelley (1986) found no variation of the O + average energy with geomagnetic activity using AE index contrary to Ohtani et al (2011) who reported a positive correlation between the O + energy and the Sym-H index. Both Lennartsson (1989) and Ohtani et al (2011) reported observations indicating a decrease of the O + average energy with increasing solar EUV flux. Lennartsson (1989) estimated that the O + decreases from ∼4-5 keV for low F10.7 to ∼2-3 keV for high F10.7 and showed that this energy decrease is weaker at high geocentric distances than at low geocentric distances.…”
contrasting
confidence: 41%
See 3 more Smart Citations